The Effect of Islamic Leadership, Islamic Spirituality, and Islamic Work Ethic on Job Satisfaction: Studies in PT bank Syariah Indonesia - Riani, Desmy; Hasnin, Hannisa Rahmaniar; Maulani, Denia; Megawati, Dewi; Syahdiany, Geny; Septiyani, Fitria Ika (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyze the extent to which Islamic Work Ethic, Islamic leadership, and Islamic spirituality influence the job satisfaction of Bank Syariah Indonesia employees. The study uses a quantitative approach with an explanatory design and a cross-sectional survey of 300 employees of Bank Syariah Indonesia at the head office and regional offices selected through purposive sampling. Data were collected using a five-point Likert scale online questionnaire and analyzed with a Partial Least Squares-based structural equation model using SmartPLS 3. The results show that Islamic leadership, Islamic spirituality, and Islamic work ethic have a positive and significant effect on job satisfaction, with Islamic leadership being the factor that has the greatest influence. These findings indicate that the alignment between work ethic, leadership style, and Islamic spirituality with the sharia organizational culture plays an important role in increasing employee job satisfaction and forms the basis for strengthening Islamic value-based human resource management policies at Bank Syariah Indonesia.